Pengaruh Penyebaran Fasilitas Sosial terhadap Sirkulasi Dalam Kota di Desa Dauh Puri Kelod Denpasar Barat - Krisanti, Nyoman Siska Dessy (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2018)
Social facilities are central to the welfare of a city.Depending on level of accessibility each infrastructure has, its uses by urban dwellers from all over town, creates a collection of complex movements which very often would generate chaotic urban circulations. An obvious implication one easily observes is a circulation deadlock taking the form as a traffic jam: a condition widely encountered by urban dwellers of DauhPuriKelod of Denpasar.This circumstance provides a ground to conduct a study of impacts of the distribution of social facilities on the urban circulation of the DauhPuriKelod area. The study first investigates the spread of the social facilities. Second, it studies traffics incurred when social facilities are accessed by urban dwellers from certain point of departures, at certain timing; and in a certain manner. And third, it analyses how these traffics contribute to the smooth operation and efficient use of urban road networks available across town. This research applies qualitative research method using naturalistic paradigm. Primary data is obtainedby conducting physical observation and individual interview. The study finds that traffic congestions taking place on circulation paths & networks across DauhPuriKelod are partially resulted by the widely spread location of numerous social facilities. This mainly due to a lack of city planning that coordinates this issue. To ease this condition, urban dwellers are strongly advised to reduce the use of private vehicles as they rely on heavily on such form of transportations at present. Keywords: Patterns of movement, inner circulation, accessibility, social facilities